Computational Screening and Experimental Evaluation of Wheat Proteases for Use in the Enzymatic Therapy of Gluten-Related Disorders - Lyudmila V. Savvateeva; Olga E. Chepikova; Alena D. Solonkina; Artemiy A. Sakharov; Neonila V. Gorokhovets; Andrey V. Golovin; Andrey A. Zamyatnin (Pharmaceuticals)
Background: Gluten-related disorders, particularly celiac disease, are triggered in susceptible individuals by the toxic effects of gluten, the major storage protein of wheat grains. This toxicity can be reduced by wheat glutenases. Members of the papain-like cysteine protease family, which can act in the human gastrointestinal tract, are promising candidates for the enzymatic treatment of celiac disease. Methods: Two wheat proteases were selected using AlphaFold2, produced in recombinant forms, and characterized. Their glutenase potentials under acidic or slightly acidic conditions were evaluated and compared with the properties of the previously characterized wheat glutenase Triticain-α. Results: All enzymes tested, Ta-P7, Ta-V6, and Triticain-α, were able to hydrolyze the model substrate (α-gliadin-derived epitope) in the pH range of 3.6–7.5. Nevertheless, Triticain-α performs the most efficient hydrolysis of the peptide substrate under the conditions of the gastrointestinal tract, according to its kinetic characteristics. In the wheat gluten degradation experiment at pH 4.6 and 37 °C, both Ta-P7 and Triticain-α cleaved the mixture almost completely within 5 min. In addition, Triticain-α and Ta-P7 significantly reduced the levels of toxic peptides compared to both intact gluten and gluten treated with pepsin-trypsin digestion as tested by the Ridascreen Gliadin Kit. Conclusions: Novel wheat proteases under investigation possess the expected glutenase activity to varying degrees; however, Triticain-α is a primary candidate for potential use in the enzymatic therapy of gluten-related disorders.